THE RELATIONSHIP BETWEEN THE FAMILY’S KNOWLEDGE AND SUPPORT WITH MENTAL DISORDERS TREATMENT IN SOUTH KONAWE DISTRICT: MENTAL DISORDERS TREATMENT - Sunding Sunding; Sunarsih Sunarsih; Timbul Supodo (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Based on the data from South Konawe District,that the prevalence of people with mental disorders in 2018 was 1 person per 1000 population up to 3 miles. Then in 2019, it increased to 2 per 1000 population up to 3 miles and in 2020 it increased again to 4 per 1000 residents up to 3 miles. The purpose of this study is to analyze the factors related to people with mental disorders treatment in South Konawe district. Methods: The type of research used is quantitative, the population in this study is all the number of people experiencing mental disorders in 2020 in South Konawe Regency as many as 214 people. The sample as many as 145 people with sampling technique Simple Random Sampling. The data analysis used is descriptive, inferential and logistic regression analysis. Result: The results showed that there was a weak relationship between family knowledge and mental disorders with phi value = 0.352, there was a weak relationship between family support and mental disorders with phi value = 0.307. Conclusion: The families with  mental health and caring for patients with mental disorders at home need to be educated, so  they can have a correct understanding about  the condition of patients with mental disorders and be able to handle patients appropriately.